Curating the gnomAD database: Report of novel variants in the thyrogobulin gene using in silico bioinformatics algorithms. (20th August 2021) - Pio, Mauricio Gomes; Siffo, Sofia; Scheps, Karen G.; Molina, Maricel F.; Adrover, Ezequiela; Abelleyro, Miguel M.; Rivolta, Carina M.; Targovnik, Héctor M.
Abstract: Thyroglobulin (TG) is a large glycosylated protein of 2767 amino acids, secreted by the thyrocytes into the follicular lumen. It plays an essential role in the process of thyroid hormone synthesis. TG gene variants lead to permanent congenital hypothyroidism. In the present work, we report a detailed population and bioinformatic prediction analyses of the TG variants indexed in the Genome Aggregation Database (gnomAD). The results showed a clear predominance of nonsense variants in the European (Finnish), European (Non-Finnish) and Ashkenazi Jewish ethnic groups, whereas the splice site variants predominate in South Asian and African/African-American populations. In total, 282 novel TG variants were described (47 missense involving the wild-type cysteine residues, 177 missense located in the ChEL domain and 58 splice site variants) which were not reported in the literature and that would have deleterious effects in prediction programs. In the gnomAD population, the estimated prevalence of heterozygous carriers of the potentially damaging variants was 1:320. In conclusion, we provide an updated and curated reference source for the diagnosis of thyroid disease, mainly to congenital hypothyroidism due to TG deficiency. The identification and characterization of TG variants is undoubtedly a valuable approach to study the TG structure/function relations and an important tool for clinical diagnosis and genetic counseling. Highlights: We report an analysis of the thyroglobulin variants indexed in the gnomAD database. A detailed population and bioinformatic analysis was performed. Missense and splice site variants were evaluated using sequence predictors. In total, 282 novel thyroglobulin variants were described. This work contributes to the knowledge of congenital hypothyroidism.